2001
DOI: 10.4049/jimmunol.167.2.995
|View full text |Cite
|
Sign up to set email alerts
|

Human Eosinophils and Human High Affinity IgE Receptor Transgenic Mouse Eosinophils Express Low Levels of High Affinity IgE Receptor, but Release IL-10 upon Receptor Activation

Abstract: FcεRI expressed by human eosinophils is involved in IgE-mediated cytotoxicity reactions toward the parasite Schistosoma mansoni in vitro. However, because receptor expression is low on these cells, its functional role is still controversial. In this study, we have measured surface and intracellular expression of FcεRI by blood eosinophils from hypereosinophilic patients and normal donors. The number of unoccupied receptors corresponded to ∼4,500 Ab binding sites per cell, whereas 50,000 Ab binding sites per ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 47 publications
2
38
0
1
Order By: Relevance
“…In the latter specimens, eosinophil degranulation was less common and tumor cells appeared more brightly fluorescent and viable. As previously reported, we found eosinophils to express low levels of the FcRI receptor but not CD23 (results not shown) (47). These results support a role for FcRI in IgE ADCC of tumor cells by eosinophils as well as monocytes.…”
Section: Eosinophils Mediate Ige-dependent Adccsupporting
confidence: 77%
See 2 more Smart Citations
“…In the latter specimens, eosinophil degranulation was less common and tumor cells appeared more brightly fluorescent and viable. As previously reported, we found eosinophils to express low levels of the FcRI receptor but not CD23 (results not shown) (47). These results support a role for FcRI in IgE ADCC of tumor cells by eosinophils as well as monocytes.…”
Section: Eosinophils Mediate Ige-dependent Adccsupporting
confidence: 77%
“…In this study, we show for the first time that a tumor Ag-specific Ab can direct eosinophils to kill tumor cells by ADCC. As observed with monocytes, and consistent with the expression of low levels of FcRI on the surface of eosinophils (47), this IgE receptor on eosinophils appears to mediate MOv18-dependent cytotoxicity of tumor cells. Engagement of IgE Abs on the surface of eosinophils triggers the release of inflammatory and cytotoxic mediators, such as eosinophil peroxidase and major basic protein (63), which may contribute to tumor cell death.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The authors concluded that eosinophils selectively release mediators as a result of stimulation of membrane receptors for immunoglobulins according to their type. Kayaba et al [82] demonstrated that the IgE-mediated ac-www.pneumonologia.viamedica.pl [79] did not observe any significant biological effect (degranulation or production of oxygen radicals or release of leukotriene C4) after the FceRI stimulation on eosinophils.…”
Section: Mechanisms Of Omalizumab Effect On Eosinophilsmentioning
confidence: 99%
“…Many IL-10-expressing cell subsets have been found, such as T h 1 cells [103][104][105], Foxp3 ? T reg cells [106][107][108], Foxp3 -T reg cells [109], B cells [110,111], macrophages [112][113][114], dendritic cells [115][116][117], neutrophils [118], and eosinophils [119]. IL-10-deficient mice are well established as a genetic model for IBD.…”
Section: Clostridium Butyricum Induces Il-10-producing Macrophagesmentioning
confidence: 99%